Hubungan antara Stres Kerja dengan Pemilihan Strategi Coping pada Perawat di Rumah Sakit Unisma Malang - Makarim, Akmal Mizan; Kurniawati P, Endah (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2014)
The purpose of this study is (1) To determine the level of stress experienced by nurses working in the Islamic Hospital Unisma Malang. (2) To determine the selection of coping strategies do nurses in Islamic Hospital Unisma Malang. (3) To determine the relationship between job stress and coping strategies in the selection of nurses at the Islamic Hospital Unisma Malang .The method used in this research is descriptive quantitative by using two variables , independent variable (X) is the stress of work and the dependent variable (Y) is a coping strategy. In this study, samples taken amounted to 75 nurses. The scale used is the Likert scale and the sampling technique used for this study is the random technique. The calculation used is the product moment correlation with aided by the software SPSS 16.0 for Windows.The results of this study, the stress experienced by nurses working in the Islamic Hospital Unisma Malang is 8 nurses (10.67%) had a high impact job stress, 44 nurses (58.67%) experienced moderate the impact of work stress, and 23 nurses (30.67%) had a low impact work stress. While the number of nurses who choose coping strategies were 37 nurses choose to use Focus Problems Coping and 38 other nurses pick Emotion Coping Focus . Based on the results it can be seen that the stress of work looks towards a positive correlation with problem focused coping. This is indicated by the number rxy = 0.095 and p = 0.418. It can be concluded despite job stress has no association with problem focused coping. While the results of the data shown job stress has a negative correlation with emotion focused towards coping. This is indicated by the number rxy = -0.186 and p = 0.110. It can be concluded despite job stress has no association with emotion focused coping.